Internet protocol over wireless sensor networks, from myth to reality - Neves, P.A.C.S. (2011)
Internet Protocol (IP) is a standard network layer protocol of the Internet architecture, allowing communication among heterogeneous networks. For a given network to be accessible from the Internet it must have a router that complies with this protocol. Wireless sensor networks have many smart sensing nodes with computational, communication and sensing capabilities. Such smart sensors cooperate to gather relevant data and present it to the user. The connection of sensor networks and the Internet has been realized using gateway or proxy- based approaches. Historically, several routing protocols were specifically created, discarding IP. However, recent research, prototypes and even implementation tools show that it is possible to combine the advantages of IP access with sensor networks challenges, with a major contribution from the 6LoWPAN Working Group. This paper presents the advantages and challenges of IP on sensor networks, surveys the state-of-art with some implementation examples, and points further research topics in this area.